A study of PALM-COEIN classification of abnormal uterine bleeding in perimenopausal women: An observational cross-sectional study - Shrestha, Sabin; Sharma, Bandana Gurung; Pandit, Chandika; Shrestha, Amisha; Karki, Pawan; Paneru, Rupa (Journal of Gandaki Medical College-Nepal, 2025)
Introduction: Abnormal Uterine Bleeding (AUB) is a common gynaecological issue affecting a large number of women of reproductive age group, especially during perimenopause. The International Federation of Gynaecology and Obstetrics (FIGO) developed a new classification system, PALM-COEIN, to standardize the terminology, diagnosis, and investigations of the causes of AUB. Therefore, this study aimed to investigate the structural (PALM) and functional (COEIN) component of the PALM-COEIN system in perimenopausal women complaining of AUB. Methods: This observational cross-sectional study was done at Gandaki Medical College, Pokhara among 100 perimenopausal women (aged 40 years and above till 1 year beyond menopause) admitted with complaints of AUB. After thorough history and examination, a clinical diagnosis was made as per PALM– COEIN classification. Analysis was done on the relative contributions of the different causes of the PALM and COEIN components. Then, endometrial sampling and hysterectomy specimen was assessed by histopathology. Results: A total of 100 women of perimenopausal age groups were studied. PALM and COEIN groups accounted for 72% and 28% respectively. Leiomyoma was the commonest cause of AUB (39%) followed by polyp (22%). Majority of the women (58%) were between 40-44 years of age, 89% were multiparous women. Overweight women (BMI of 25 to 29.99) were 47%. Proliferative endometrium (37.14%) was the most common histopathological finding, followed by secretory endometrium (22.85%). Conclusions: In perimenopausal women with abnormal uterine bleeding, leiomyoma was the most common structural cause, and proliferative endometrium was the most common non-structural cause. None of the cases were found to have malignancy or coagulopathy